Why Doesn’t Japan have a Natural Gas Pipeline Network? Consideration from the Determinant of the Choice between LNG Tank Trucks and Pipelines - Hashimoto, Satoru (International Journal of Energy Economics and Policy, 2021)
This study considers the importance of comprehensive pipeline network plans with exploring the determinants of vertical integration in Japan’s natural gas distribution utilities from the perspective of transaction cost economics. Japan’s natural gas industry is reliant on imported liquefied natural gas (LNG) that normally requires regasification prior to consumption. Unbundling of the industry has not been enforced and while some local distribution utilities purchase gas via pipelines that is regasified by the seller, others choose LNG from tank trucks with subsequent regasification occurring in-house (vertical integration). Estimating the determinants of vertical integration in terms of transaction cost economics, I deduce the cause of poor pipeline networks in Japan. This study found that local distribution utilities prefer to purchase natural gas via pipelines when there are neighboring wholesalers or utilities. Hence, a broad pipeline network has never been constructed because local distribution utilities construct point-to-point pipelines to neighboring utilities or wholesalers. This indicates that without pipeline network planning by the government, comprehensive infrastructure policies, or financial support, a broad pipeline network will not be built throughout the country. Keywords: Natural Gas, Transaction Costs, Probit model, Pipeline Networks. JEL Classifications: Q40, L95, L81 DOI: https://doi.org/10.32479/ijeep.11049